Cyclic mismatch binding ligands interact with disease-associated CGG trinucleotide repeats in RNA and suppress their translation - Konieczny, Patryk; Mukherjee, Sanjukta; Stepniak-Konieczna, Ewa; Taylor, Katarzyna; Niewiadomska, Daria; Piasecka, Agnieszka; Walczak, Agnieszka; Baud, Anna; Dohno, Chikara; Nakatani, Kazuhiko; Sobczak, Krzysztof (Oxford University Press, 2021)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is a late-onset neurodegenerative disorder caused by a limited expansion of CGG repeats in the FMR1 gene. Degeneration of neurons in FXTAS cell models can be triggered by accumulation of polyglycine protein (FMRpolyG), a by-product of translation initiated upstream to the repeats. Specific aims of our work included testing if naphthyridine-based molecules could (1) block FMRpolyG synthesis by binding to CGG repeats in RNA, (2) reverse pathological alterations in affected cells and (3) preserve the content of FMRP, translated from the same FMR1 mRNA. We demonstrate that cyclic mismatch binding ligand CMBL4c binds to RNA structure formed by CGG repeats and attenuates translation of FMRpolyG and formation of nuclear inclusions in cells transfected with vectors expressing RNA with expanded CGG repeats. Moreover, our results indicate that CMBL4c delivery can reduce FMRpolyG-mediated cytotoxicity and apoptosis. Importantly, its therapeutic potential is also observed once the inclusions are already formed. We also show that CMBL4c-driven FMRpolyG loss is accompanied by partial FMRP reduction. As complete loss of FMRP induces FXS in children, future experiments should aim at evaluation of CMBL4c therapeutic intervention in differentiated tissues, in which FMRpolyG translation inhibition might outweigh adverse effects related to FMRP depletion.
Keywords: fragile X-associated tremor/ataxia syndrome; FXTAS; repeat-associated non-AUG (RAN) translation; RAN translation; CGG repeats; cyclic mismatch binding ligands; CMBL; CMBLs